(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Pleural effusion can be transudate or exudate. The cause of transudate formation is usually congestive heart failure, mainly left ventricular failure, and in patients with pericarditis, accumulation of transudate (hydrothorax), the pleura is not involved in the primary pathological process.